Comparison of Conventional Inflammatory Parameters with Tumor Necrosis Factor- α Levels in Different Stages of Diabetic Retinopathy and Non-Diabetic Controls - Metin Guclu (Medicine Science, 2015)
Aim of this study was to identify the risk factors associated with diabetic retinopathy in patients with Type 2 diabetes mellitus(DM), and to compare the levels of erythrocyte sedimentation rate (ESR), high sensitive CRP(hs-CRP) and tumor necrosis factor-α (TNF-α), in patients with every stage of diabetic retinopathy and non-diabetic healthy controls. A total of 79 individuals, 64 diabetic and 25 healthy controls were included in the study. Patients were divided into three groups. Group 1 consisted of those without diabetic retinopathy (DR) (n=26), group 2 with non-proliferative (NPDR) (n=19), and group 3 with proliferative diabetic retinopathy (PDR) (n=19). Even though the similar age distribution, disease duration were different as 6.9 ± 6.5, 10.3 ± 5.4, and 12.7 ± 5.1 years in Group 1, Group 2 and Group 3, respectively (p>0.001). The majority of the patients with PDR were male, had high levels of albuminuria and high percents of receiving insulin treatment (p [Med-Science 2015; 4(3.000): 2364-78]